Environmental impact of the broiler production chain under conventional systems - Portillo-Chávez, Felipe (2025)
Introduction. Broiler production is an activity of increasing economic importance worldwide, but it entails a significant environmental impact. Objective. To assess the environmental impact of conventional broiler production chain systems. Materials and methods. The life cycle analysis (LCA) methodology was used following a “cradle to gate” approach. Base parameters were collected from a poultry farm located in San Ramón, Alajuela, Costa Rica, during the period January through December 2021. The LCA functional unit was defined as one metric ton of chicken meat (MT CM). Environmental impact categories were analyzed using the ReCiPe 2016 v.1.1 system, with characterization factors at the midpoint level under a hierarchical perspective. Results. The estimated environmental impacts, expressed in equivalent units per MT CM were as follows: global warming, 5208 kg CO2-eq; terrestrial acidification, 52.6 kg SO2-eq; marine eutrophication, 4.19 kg Neq; freshwater eutrophication, 2.47 kg P; land use, 5238 m2 crop year; water consumption, 3962 m3; terrestrial ecotoxicity, 1831 kg 1,4-DCB; marine ecotoxicity, 2.79 kg 1,4-DCB; freshwater ecotoxicity, 8.49 kg 1,4-DCB; human toxicity (carcinogenic), 1.13 kg 1,4-DCB; human toxicity (non-carcinogenic), 84.4 kg 1,4-DCB; fine particulate matter formation, 8.15 kg PM2.5; fossil resource depletion, 246.1 kg oil; ozone formation (ecosystem health), 10.8 kg NOx; ozone formation (human health), 10.7 kg NOx, and stratospheric ozone depletion, 0.043 kg CFC11. Conclusions. The processes contributing most significantly to the environmental impacts evaluated in this study were the production of feed, fertilizers, and fuels, along with farm waste management. The majority of the environmental impact attributable to the broiler production chain occurs outside of Costa Rica’s borders.